Description of three species of Halmyrapseudes (Crustacea: Tanaidacea: Parapseudidae), with a discussion of biogeography - Kakui, Keiichi; Angsupanich, Saowapa (Zootaxa, 2013)
We describe Halmyrapseudes gutui sp. nov. from a mangrove area on Lidee Island, southern Thailand. This species closely resembles H. cooperi, H. killaiyensis, and H. thaumastocheles, but differs in having the lacinia mobilis with three teeth, and the pereopod 1 carpus with 0,1 or 1,1 ventral simple setae proximal to each spiniform seta. We redescribed and synonymized two species of questionable affiliation, Apseudes cooperi and A. digitalis, placing them in Halmyrapseudes, and partly redescribed Halmyrapseudes killaiyensis. Halmyrapseudes and Pseudohalmyrapseudes have disjunct distributions. Halmyrapseudes is similar in distribution to two freshwater fish taxa whose distributions are considered to reflect the breakup of Gondwana and subsequent continental drift. Pseudohalmyrapseudes occurs around Australia, and its distribution seems to be separated from that of Halmyrapseudes by Wallace’s Line or Huxley’s Line, which are distributional barriers for both terrestrial organisms and an amphidromous shrimp. The adjacent distributions and morphological similarities suggest that Halmyrapseudes and Pseudohalmyrapseudes are sister taxa.